The Influence Of Interpersonal Communication And Supervision On Nursing Performance And Motivation As Intervening Variables In The Infatient Installation Of Sekayu Hospital - Efriena Masda Kartianah; Mohamad Adam; Zunaidah, Zunaidah (International Journal of Health Engineering and Technology, 2024)
The problem of nursing staff performance is a fundamental problem that will always be encountered in hospital management.The phenomenon in this research is the existence of performance that has not satisfied the community regarding the services received. Factors that influence the performance of nursing staff can be influenced by individual characteristics(communication),psychological (motivation), and organizational factors (supervision/supervision system). The aim of this research is to obtain empirical evidence of the influence of interpersonal communication on motivation, supervision on motivation, interpersonal communication on performance, supervision of performance, motivation on performance, interpersonal communication on performance through motivation, and the influence of supervision on performance through motivation. This research uses descriptive statistics with quantitative data and SEM (Structural Equation Model) with the Smart PLS application, with a sample size of 148 nursing staff in the Sekayu Hospital Inpatient Installation. It was found that the majority of nursing staff were aged 20 - 30 years as much as 62.84%, the majority of nursing staff were women, namely 77.03%, the majority of nursing staff with Diploma III education level was 71.62%, 75% of positions were Executive Nurses/Midwives. , and the maximum work period is in the range of 3 – 5 years, namely 61.49%. There is a significant influence between interpersonal communication and motivation, and supervision and motivation. There is no significant influence between interpersonal communication on supervision performance and performance, motivation and performance, interpersonal communication and performance through motivation, supervision and performance through motivation in nursing staff at the Sekayu Hospital Inpatient Installation.